Evaluation of Sarcocephalus latifoliusAfzel. ex R.Br. Rubiaceae on Reduction of Creatinine Level and Its Antioxidant In-Vitro - Obika, Ogochukwu Immaculate; Oyawaluja, Aminat Asabi; Odukoya, Olukemi Abiodun; Obika-Ndiri, Ngozi Afulenu; Oiseoghaede, Joseph Oisemuzeimen (Journal of Fundamental and Applied Pharmaceutical Science, 2024)
Medicinal herbs are divine gifts from Mother Nature and have been used for centuries as natural remedies. Sarcocephalus latifolius has been reported to contain active substances that have therapeutic effects on the kidney. The study aims to investigate the medicinal effects of Sarcocephalus latifolius extract on creatinine levels. Phytochemical and antioxidant activity were carried out using standard methods. Vacuum Liquid chromatography and Thin Layer Chromatography were employed to separate constituents of the plant extract, which were then evaluated for their creatinine reduction ability using Jaffe’s method. Based on the IC50, which is half the maximal inhibitory concentration value, Sarcocephalus latifolius demonstrates stronger antioxidant activity at 43.34µg/ml compared to the standard ascorbic acid at 40.59µg/ml. The Two-way ANOVA Statistical analysis revealed significant differences between the patients’ urine (rows) as the P-value = 6.17×10-16 is less than 0.05 significant level, and the dose treatments (columns) as the P-value = 1.71×10-12 is less than 0.05 significant level. Fractions of Sarcocephalus latifolius at various concentrations exhibit varied effects on creatinine levels, which could be attributed to the bioactive compounds in the fractions. Sarcocephalus latifolius showed potential for creatinine reduction, especially at low doses.